Evaluasi Performa Dye Senstized Solar Cell dengan Lapisan Fiber Tissue Kontinue - Saputri, Rizky Ayu; Prayoga, Agung; Ramadhani, Imes Suci; Pratama, Filli; Tamrin, Tamrin (Seminar Nasional Lahan Suboptimal, 2024)
Saputri, R. A., Prayoga, A., Ramadhani, I. S., Pratama, F., & Tamrin, T. (2024). Evaluation of dye sensitized solar cells performance with continuous fiber tissue layer. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 344–357).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of the factors that can affect DSSC performance are electrolytes. The addition of continuous fiber tissue can improve DSSC performance by maintaining electron continuity because electrolytes are always available. The fiber tissue used in this study was facial tissue. This research was studied the differences in the width of the continuous fiber tissue layer as an electrolyte provider on the performance of dye sensitized solar cells, especially efficiency and fill factor. This study used several series, namely: preparation of the DSSC structure, arrangement and assembly of the DSSC layer, and measurement of the DSSC. The variations in the width of the continuous fiber tissue layer used in this study were 1 cm, 1,5 cm, and 2 cm. The research parameters observed in this study were: current and voltage measurements, power calculations, Fill Factor measurements, and DSSC efficiency calculations. The results of the study showed that the performance of DSSC with the addition of continuous fiber tissue layers with variations in width had higher performance than DSSC without additional treatment. The best DSSC performance using the addition of continuous fiber tissue was found in experimental unit B with a width of 1,5 cm, namely Isc: 0,0269 mA, Voc: 731 mV, Imax: 0,0103 mA, Vmax: 472 mV, Pmax: 5,0504 µW, FF: 0,257, and an efficiency of 0,01912%.